Efektivitas Digital Marketing dalam Mempromosikan Event Olahraga di Maluku - Rumawatine, Ztella; Febriani, Laili Nabela; Pujiati, Amin (MANGGUREBE: Journal Physical Education, Health and Recreation, 2025)
Digital marketing has become a crucial instrument in promotional efforts for various types of events, including sporting events. In the Maluku region, the implementation of digital marketing strategies in promoting sports events has had a significant impact on increasing public participation and awareness. This article aims to analyze the effectiveness of digital marketing in this context by examining the methods applied, the results achieved and the challenges faced. Through an approach based on data analysis and case studies, this research explores the extent to which digital marketing can be an effective means of expanding the reach of information and increasing public involvement in sporting events. By understanding the dynamics of the use of digital marketing, this research is expected to provide insight into more optimal marketing strategies for sports event organizers in Maluku, as well as identify obstacles that need to be overcome to increase the effectiveness of digital promotions.